Utilization of Dimethyl Fumarate and Related Molecules for Treatment of Multiple Sclerosis, Cancer, and Other Diseases - Al-Jaderi, Zaidoon; Maghazachi, Azzam A. (Frontiers in Immunology, 2016)
Several drugs have been approved for treatment of multiple sclerosis. Dimethyl fumarate (DMF) is utilized as an oral drug to treat this disease and is proven to be potent with less side effects than several other drugs. On the other hand, monomethyl fumarate (MMF), a related compound has not been examined in greater details although it has the potential as a therapeutic drug for multiple sclerosis and other diseases. The mechanism of action of DMF or MMF is related to their ability to enhance the antioxidant pathways and to inhibit reactive oxygen species. However, other mechanisms have also been described which include effects on monocytes, dendritic cells, T cells, and natural killer cells. It is also reported that DMF might be useful for treating psoriasis, asthma, aggressive breast cancers, hematopoeitic tumors, inflammatory bowel disease, intracerebral hemorrhage, osteoarthritis, chronic pancreatitis, and retinal ischemia. In this article we will touch on some of these diseases with an emphasis on the effects of DMF and MMF on various immune cells.